Structure of the epididymis and ductus-deferens of Black Bengal buck (Capra hircus): a light microscope study - DATTA, UTTAM; RAY, S; BASU, S; NANDI, P R; RAY, K; GHOSH, D (The Indian Journal of Animal Reproduction, 2023)
Histological study of the epididymis in Black Bengal buck indicated a gradual decrease of epithelialheight and an increase in tubular diameter from caput to caudal epididymal region. Spermatozoa)distribution in the tubular lumen were found less in number in caput followed by gradual increase towardscauda .. Maximum number of basal cells was found in the corpus region. Ductus- deferens was characterizedby long mucosa) folds.
Keywords: Epididymis; ductus-deferens